The Foundation of Monte Albán, Intensification, and Growth: Coactive Processes and Joint Production - Nicholas, Linda M.; Feinman, Gary M. (Frontiers in Political Science, 2022)
Most early sedentary villages (c. 1500–500 BCE) in the Valley of Oaxaca, Mexico, were situated on or near well-watered land. Around 500 BCE, a new hilltop center, Monte Albán, was established at the nexus of the valley's three arms, where agriculture was far riskier due to unreliable rainfall and a dearth of permanent water sources. During the era of its establishment, not only was Monte Albán larger than any earlier community in the region, but many other settlers moved into the rural area around Monte Albán. This marked shift in settlement patterns in the Valley of Oaxaca and the underlying processes associated with the foundation of Monte Albán have long been debated. How can we account for the immigration of people, some likely from beyond the region itself, to an area where they faced greater risks of crop failure? One perspective, reliant on uniform models of premodern states as despotic, viewed the process from a basically top-down lens; leaders coerced subalterns to move near the capital to provide sustenance for the new center. Yet more recent research has found that governance at Monte Albán was generally more collective than autocratic, and productive activities were centered in domestic units and not managed from above. Based on these new empirical foundations, we reassess earlier settlement and land use studies for the Valley of Oaxaca and view this critical transition as initiated through coactive processes in which new institutions were formed and new relations forged. Shifts in defense, ritual, domestic organization, craft production, and exchange all coincided with this episode of growth fostered by joint production, which intensified agrarian yields through increased domestic labor investments.